2019
DOI: 10.1128/aem.01077-19
|View full text |Cite
|
Sign up to set email alerts
|

Pseudofructophilic Leuconostoc citreum Strain F192-5, Isolated from Satsuma Mandarin Peel

Abstract: Fructophilic lactic acid bacteria (FLAB), composed of Fructobacillus spp., Lactobacillus kunkeei, and Lactobacillus apinorum, are unique in that they prefer d-fructose over d-glucose as a carbon source. Strain F192-5, isolated from the peel of a satsuma mandarin and identified as Leuconostoc citreum, grows well on d-fructose but poorly on d-glucose and produces mainly lactate and acetate, with trace amounts of ethanol, from the metabolism of d-glucose. These characteristics are identical to those of obligate F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…For TPW, we found only a few studies that showed the value of its microorganisms, such as the study of Ling et al [ 288 ] that has focused to identify new endophytic yeast strains able to produce Indole-3-acetic acid (IAA) from TPW. Also, Maeno et al [ 289 ] have isolated Pseudofructophilic Leuconostoc citreum Strain F192-5 from TPW able to produce mainly lactate and acetate, with trace amounts of ethanol, from d -glucose metabolism. For PPW, El Barnossi et al [ 283 ] have isolated and identified a Bacillus sp.…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
“…For TPW, we found only a few studies that showed the value of its microorganisms, such as the study of Ling et al [ 288 ] that has focused to identify new endophytic yeast strains able to produce Indole-3-acetic acid (IAA) from TPW. Also, Maeno et al [ 289 ] have isolated Pseudofructophilic Leuconostoc citreum Strain F192-5 from TPW able to produce mainly lactate and acetate, with trace amounts of ethanol, from d -glucose metabolism. For PPW, El Barnossi et al [ 283 ] have isolated and identified a Bacillus sp.…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
“…Lactobacillus kosoi, isolated from a sugar-vegetable fermented beverage [21], was recently classi ed as a member of the genus Apilactobacillus [10] but was only recently considered a later heterotypic synonym of A. micheneri [22]. Recent study found a strain of Leuconostoc citreum showing FLAB-like poor D-glucose metabolic property, due to the absence of an active promoter region upstream of the adhE gene [14]. The strain showed distinct genomic characteristics from FLAB, and the strain was thus classi ed as pseudo-FLAB.…”
Section: Discussionmentioning
confidence: 99%
“…The growth characteristics was due to an inactivation of the adhE gene by deletion of the promoter region upstream of the gene [14]. However, the strain did not have speci c reduction of total CDS and genes involved in carbohydrate transport and metabolism, observed in typical FLAB, and the strain was thus described as pseudo-FLAB.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“… 71 Assembly and annotation of the sequences, and quality check of the resulting genomic data were conducted by methods described previously. 72 The genomic data were used to search for GH family enzymes using dbCAN2 in the CAZy database with HMMER, DIAMOND, and Hotpep tools. 73 GH proteins were identified when detected by two of the three tools, as recommended by the database.…”
Section: Methodsmentioning
confidence: 99%